PHARMACOGNOSTIC AND PHYSICO-CHEMICAL INVESTIGATION OF BARK OF PUTRANJIVA ROXBURGHII WALL (EUPHORBIACEAE) - KEDAR KALYANI ABHIMANYU; DR. CHAUDHARI SANJAY RAVINDRA; DR. RAO SRINIVASA AVANAPU (International Journal of Pharma and Bio Sciences, 2015)
Putranjiva roxburghii Wall (syn. Drypetes roxburghii Wall.) of Euphorbiaceae family is an evergreen tree of tropical region often cultivated as avenue tree along the road side. The Objective of the study was to develop various standardization parameters for the evaluation of trunk bark science it is largely used to cure certain ailments. Morphology, histology, powder characteristics and Scanning Electron Microscopy (SEM) of bark were observed and results were recorded. Physico-chemical parameters such as total ash value (13.5%) w/w, moisture content (6%) w/w, foaming index (less than 100), total tannin content (5% w/w), Crude fibres residue ( 32%) w/w, Fluorescence analysis, extractive value includes pet ether soluble extractive value (3.45%), ethanol (3.90%), ethyl acetate(5.14%) and aqueous extract(3.5%) w/w were analysed by chemical test and shows presence of saponins, tannins, steroids, triterpenoids. So these parameters are usefull in the authentication of Putranjiva roxburghii Wall. However the phytochemical analysis of bark of Putranjiva roxburghii in the present work is first of its kind used for the pharmacognostic and phytochemical evaluation.